Pendampingan Ibu Balita Melalui Model Edukasi Gizi Berbasis Aplikasi Digital untuk Pencegahan Stunting di Kabupaten Brebes - Arif Setia Sandi A.; Deny Nugroho Triwibowo; Azhar Bashir; Sony Kartika Wibisono; Fitri Ayuningtyas; Iis Setiawan Mangku Negara (Universitas Methodist Indonesia, 2025)
Stunting is a chronic nutritional problem requiring sustainable intervention, particularly in priority areas such as Brebes Regency. Conventional nutritional interventions often lack sustainability in monitoring child growth and development. This program aims to evaluate the effectiveness of the Digital Application-Based Nutrition Education Model (Si Penting)—a collaboration between Universitas Harapan Bangsa and Universitas Muhammadiyah Brebes—in strengthening caregiver capacity. The activity was conducted in Bantarkawung Sub-district, involving 45 caregivers of toddlers aged 6–24 months. A one-group pre-test post-test design was employed. The intervention consisted of face-to-face nutrition education followed by training and mentoring on the Si Penting Digital Application for two weeks. This program emphasized intensive mentoring for caregivers to operate the application for independent monitoring. Results showed a significant increase in participants' knowledge and attitudes (p<0.05), followed by proactive behavioral changes in monitoring child growth. The intervention model was successful, as shown by a 95.6% adoption rate for the application. It is concluded that the Digital Application-Based Nutrition Education Model effectively helped caregivers improve their ability to monitor nutrition on their own and is suggested to be used alongside Posyandu services to create lasting benefits in lowering stunting risks.